(untitled) (Journal of International Studies, 2020)
This paper highlights the findings of a study carried out on Infonnation Technology outsourcing (ITO) experience of eighty three Malaysian companies. ITO is by no means new in Malaysia as some companies indicated that they have been outsourcing for at least ten years. This study provides an insight of ITO practices in Malaysia. The study examines the level of ITO, IT services that are most often outsourced, types of ITO arrangements, and the motivations behind the use of this option. It was discovered that the most commonly outsourced IT services are those related to application and software developments and a majority of the companies practice the partial outsourcing approach. In addition, the study also illustrated, that a higher proportion of the companies are outsourcing their IT services to local vendors.